Nanocarriers-Mediated Drug Delivery Systems for Anticancer Agents: An Overview and Perspectives [Corrigendum] - Edis Z (Dove Medical Press, 2021)
Edis Z, Wang J, Waqas MK, Ijaz M, Ijaz M. Int J Nanomedicine. 2021;16:1313–1330. The authors have advised affiliation 3 on page 1313 is incorrect. The text “Affiliated Hospital of Youjiang Medical College for Nationalities” should read “Affiliated Hospital of Youjiang Medical University for Nationalities”. The authors apologize for this error. Read the original article